RUANG PEREMPUAN SASAK: PERAN ARSITEK DALAM PELESTARIAN TRADISI NENSEK - Liza Hani Saroya Wardi; Muhammad Fadjri; Barzian Al-Kitab; Nurlael Fikri Ahmad; Ilham Malik; Vania Aurel Aurora; Luvena Akmalia Puteri Al-Rayyan; Asstiananda; Nurannisa; Asstiananda Asstiananda; Nurannisa Nurannisa (Journal of Innovation Research and Knowledge, 2025)
This study describes the role of architects in the participatory design of Sasak women's spaces in the nensek tradition in Keloke Aik Atas Hamlet, Batujai Village, West Praya District, Central Lombok Regency. Through the active involvement of Sasak women in Keloke Aik Atas from the research, design to empowerment stages, the concept of a realized space reflects their own ideals and collective memories is presented. The method used is a participatory approach through in-depth interviews, observations and analyzed using hermeneutics and semiotic approaches. The research findings include the existence of spaces that illustrate the ideals of Sasak women to always meet their ancestors as well as a medium for their meetings with their future generations. The design results in the form of a women's space as a learning space for the nensek tradition which is expected to become a learning space for the nensek tradition so that the nensek tradition remains preserved forever. Not only that, the learning space for the nensek tradition can be the basis for the development of an educational tourism hamlet to encourage economic growth as well as social change in the community in the hamlet